2020
DOI: 10.1038/s41598-020-63312-0
|View full text |Cite|
|
Sign up to set email alerts
|

Arctic avian predators synchronise their spring migration with the northern progression of snowmelt

Abstract: Migratory species display a range of migration patterns between irruptive (facultative) to regular (obligate), as a response to different predictability of resources. In the Arctic, snow directly influences resource availability. The causes and consequences of different migration patterns of migratory species as a response to the snow conditions remains however unexplored. Birds migrating to the Arctic are expected to follow the spring snowmelt to optimise their arrival time and select for snow-free areas to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…Stopovers on waterbodies that were still frozen may provide good visibility when scanning for prey and good camouflage against the still-white ice. Recent work showed that Snowy Owls closely followed the receding snow line (Curk et al 2020) and we suggest the presence of ice on lakes and oceans may be an attractive feature correlated with the timing of snowmelt that may persist on the landscape a few weeks after snow cover has disappeared.…”
Section: Location and Function Of Stopoversmentioning
confidence: 50%
See 2 more Smart Citations
“…Stopovers on waterbodies that were still frozen may provide good visibility when scanning for prey and good camouflage against the still-white ice. Recent work showed that Snowy Owls closely followed the receding snow line (Curk et al 2020) and we suggest the presence of ice on lakes and oceans may be an attractive feature correlated with the timing of snowmelt that may persist on the landscape a few weeks after snow cover has disappeared.…”
Section: Location and Function Of Stopoversmentioning
confidence: 50%
“…Such tactics, however, may not apply to species such as Snowy Owls Bubo scandiacus, which do not have a fixed breeding site that is their destination. After reaching the breeding range, Snowy Owls must prospect, apparently nomadically, as they seek out appropriate areas with high food abundance on which to settle (Therrien et al 2014, Curk et al 2020. Hence, movements within the breeding range may be used primarily to prospect for lemming peaks, as Snowy Owls will only settle to breed in areas of high lemming abundance (Gauthier et al 2013, Therrien et al 2014, Robillard et al 2016.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spatiotemporal variation in the availability and depletion of energy has consequences resulting in, for example, the mass-movement tracking of resources [41,58,59] and thus animal migration (i.e., following a resource wave). As we begin to understand the value of energy as a single currency and its variation, social sampling should facilitate gradient-tracking across landscapes, including regional and seasonal gradient-tracking, that gives rise to a concerted energy wavenamely balancing and synchronising the tracking of good conditions for movement (such as winds, currents or substrates) with good conditions for foraging (such as green-up [60] or snow melt [61]) and safe conditions of refuge (away from predator activity), simultaneously.…”
Section: Open Accessmentioning
confidence: 99%
“…2018). Snowy Owls from the central regions of North America appear to follow similar and constant migration routes from breeding to winter areas (Curk et al 2020; K. L. Wiebe personal communication), and other studies concluded there was some site fidelity to wintering areas by Snowy Owls (Therrien et al . 2011, Robillard et al .…”
Section: Introductionmentioning
confidence: 97%